Characterizing conflict between humans and big cats Panthera spp: A systematic review of research trends and management opportunities - Krafte Holland, Kathleen; Larson, Lincoln R.; Powell, Robert B. (PLOS ONE, 2018)
Conservation of big cats (Panthera spp.), a taxonomic group including tigers, lions, jaguars, leopards and snow leopards, is a daunting challenge. As expanding human populations across Panthera range countries exacerbate competition for land and prey, conflicts between humans and big cats are inevitable. Through a systematic review of the peer-reviewed literature published from 1991 to 2014 and indexed in Web of Science and Google Scholar (186 articles), our study explored the current state of knowledge regarding human-Panthera conflict and potential solutions, examining variables such as spatial and temporal distribution of research, methods used to study conflict, evaluation of interventions, and management recommendations. Our synthesis revealed several key data gaps and research needs. More studies could utilize diverse data collection approaches to focus on both the ecological and socio-cultural context for conflict. Additionally, only 21% of articles included in the review evaluated conflict mitigation interventions, and few of these yielded conclusive results. Success ratios suggest that compensation schemes and livestock management strategies were more effective tools for addressing conflict than either direct interventions (lethal removal or translocation of animals) or community interventions (e.g. education, ecotourism, local management). More studies should systematically evaluate the efficacy of conflict mitigation strategies, many of which are consistently recommended without empirical support. Results highlight trends and opportunities that can be used to inform future research and management efforts focused on human-Panthera conflict, ultimately enhancing the potential for coexistence between humans and carnivore species worldwide.